2004
DOI: 10.1158/0008-5472.can-04-1547
|View full text |Cite
|
Sign up to set email alerts
|

Cdc7 Inhibition Reveals a p53-Dependent Replication Checkpoint That Is Defective in Cancer Cells

Abstract: Cdc7 is an evolutionarily conserved kinase that regulates S phase by promoting replication origin activation. Down-regulation of Cdc7 by small interfering RNA in a variety of tumor cell lines causes an abortive S phase, leading to cell death by either p53-independent apoptosis or aberrant mitosis. Unlike replication fork blockade, Cdc7-depleted tumor cells do not elicit a robust checkpoint response; thus, inhibitory signals preventing additional cell cycle progression are not generated. In normal fibroblasts, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

27
162
0
2

Year Published

2006
2006
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 131 publications
(191 citation statements)
references
References 44 publications
27
162
0
2
Order By: Relevance
“…In striking contrast, normal cells avoid entering S phase with a reduced number of replication-competent origins by engaging a recently described cell cycle checkpoint, the 'origin activation checkpoint'. Several studies have shown that following impairment of the DNA replication initiation machinery, normal cells arrest at the G 1 -S boundary with unreplicated DNA, elevated p53 levels and induction of CDKI p21 [111,125,126]. We discovered that the molecular architecture of the underlying cell cycle checkpoint is critically dependent on several tumour suppressor proteins, including p53, p21, Dkk3, ARF, Hdm2, FoxO3a, p15, p27 and RB [129] (Figure 4A).…”
Section: The Dna Replication Initiation Machinery-a Promising Anti-camentioning
confidence: 81%
See 2 more Smart Citations
“…In striking contrast, normal cells avoid entering S phase with a reduced number of replication-competent origins by engaging a recently described cell cycle checkpoint, the 'origin activation checkpoint'. Several studies have shown that following impairment of the DNA replication initiation machinery, normal cells arrest at the G 1 -S boundary with unreplicated DNA, elevated p53 levels and induction of CDKI p21 [111,125,126]. We discovered that the molecular architecture of the underlying cell cycle checkpoint is critically dependent on several tumour suppressor proteins, including p53, p21, Dkk3, ARF, Hdm2, FoxO3a, p15, p27 and RB [129] (Figure 4A).…”
Section: The Dna Replication Initiation Machinery-a Promising Anti-camentioning
confidence: 81%
“…This would translate into low therapeutic indices often found for conventional chemotherapeutic drugs targeting the cell cycle. However, potent cancer cell-specific killing has been demonstrated in preclinical models after inhibition of origin licensing [125] or, alternatively, origin activation through targeting Cdc7 kinase [111,118,126,127]. Tumour cell specificity is thought to result from transformed cells entering S phase with inadequate numbers of competent origins to complete chromosomal replication.…”
Section: The Dna Replication Initiation Machinery-a Promising Anti-camentioning
confidence: 99%
See 1 more Smart Citation
“…32 However, other experimental evidence suggested that p53 is required for the lasting maintenance of the replication checkpoint. 33 We used HCT116 p53−/− , a p53-null HCT116-derived cell line 24 ( Figure 3B), to test whether p53 is required for the 5-ASA-induced S-phase accumulation ( Figure 3C, lower panels). Upon treatment with 5-ASA, p53-null cells showed a replication arrest very comparable with that of the p53 wild-type population (percentage S phase-HCT116 p53−/− : 0 mmol/L: 47.4% ± 2.9%; 10 mmol/L: 59.7% ± 2.1%, P <.0001), indicating that p53 does not have a causative role in the 5-ASA-mediated cell cycle arrest.…”
Section: -Asa-induced S-phase Accumulation Is P53-independentmentioning
confidence: 99%
“…10,11 Because Cdc7 overexpression promotes proliferation and survival of certain tumor cells, knockdown of Cdc7 by siRNA has led to p53-independent apoptosis in cancer cell lines. 12,13 Tumor cells with the often impaired S-phase checkpoints progress to mitosis without DNA repair. Meanwhile, upon Cdc7 depletion, normal cells are able to arrest in the G1 phase of the cell cycle and resume normal divisions once an initiation process is restored.…”
mentioning
confidence: 99%